The UCL Institute of Education From training college to global institution - Aldrich, Richard (UCL Press, 2021)
The history of the UCL Institute of Education is one of persistent renewal. Since its founding in 1902 as the London Day Training College, through its establishment as a university institute and merger with UCL, the IOE has constantly grown into new areas of learning and social research. As a locus for leadership, it has exerted influence upon the nature and direction of education nationally and internationally. Drawing upon a wide range of sources, the connections between internal history and external historical developments are sensitively teased out. The result is an elegantly written history, characterised by substantial scholarship and analysis, and enlivened by illustrations and anecdote. The pages of this book are peopled with some of the most influential, and at times controversial, figures of education, including Sidney Webb, Cyril Burt, Susan Isaacs, Sophie Bryant, Richard Peters, Basil Bernstein, Ann Oakley, Celia Hoyles and Stephen Ball. Two new chapters extend Richard Aldrich's text to 2020. These examine the extraordinary years of growth in the early 2000s, followed by a period of consolidation, merger with UCL and subsequent expansion. The IOE is unique in successfully pursuing a world-leading research agenda while also supporting a wide range of teacher education, having an impact in London, across Britain and the world.